Researches regarding the use of non-conventional actuators - Duțu, I.C.; Axinte, T.; Maican, E.; Frățilă, C.; Damian, R.G.; Curcă, E.; Badanau, V. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The purpose of this article is to present relevant concepts about the study of electro-pneumatic circuits using fluidic muscle actuators. The fluidic muscle is a type of pneumatic actuator having an extensive history of technical applications in the biomechanical field since the 1955. After Introduction, the authors study two pneumatic circuits. In fact, the first pneumatic circuit in this paper has only one actuator (fluidic muscle 1-1), but the second pneumatic circuit has two actuators (fluidic muscles 2-1 and 2-2. Further on, the authors present two electro-pneumatic schematics, a simple electro-pneumatic circuit and another electro-pneumatic circuit with PLC (Programmable Logic Controller). This type of actuator is used in robotics, material handling, motion control, industrial field and other applications. The pneumatic and electro-pneumatic circuits given in this paper are made using FluidSim software from Festo. In this case, the fluidic muscles are only non-conventional actuators. However, in pneumatic installations as well as in electro-pneumatic installations, the non-conventional actuators have the following advantages: strength, compactness, reliability, low price, ease of assembly or disassembly from their circuits, etc. Of course, in practice are many types of fluidic muscles, which are used in electro-pneumatic installations.